Construct validity of the Quality of Upper Extremity Skills Test for children with cerebral palsy - Thorley, M.; Lannin, N.; Cusick, A.; Novak, I.; Boyd, Roslyn (2012)
Aim: The aim of the study was to investigate the construct validity of the Quality of Upper Extremity Skills Test (QUEST) in children with cerebral palsy (CP). Method: A total of 170 QUEST assessments from a convenience sample of 94 children with CP involved in clinical and research treatment programmes (54 males, 40 females; mean age 6y 10mo, SD 2y 11mo, range 2-16y; Gross Motor Function Classification System levels I-V) were reviewed. Results: The QUEST was not unidimensional; many items demonstrated poor fit when total scores were analysed; goodness of fit improved when domains were considered independently and limbs separately examined. QUEST items involving elbow flexion and/or forearm in pronation were easily achieved, thus reducing test sensitivity. Postures items in the grasp domain behaved erratically, with little total score relationship. Interpretation: Calculating total scores is discouraged. Reporting QUEST results separately for domains and each limb is recommended. Posture items in the grasp domain had little relationship with total scores and it is recommended that they be removed from the test.